Bemerkungen zur Struktur der japanischen Unternehmensleitung nach den jüngsten gesellschaftsrechtlichen Reformen - Rodatz, Peter (Zeitschrift für Japanisches Recht, 2003)
This article discusses the structure of boards of Japanese corporations and the possible implications of recent reforms of company law on these structures. Because a significant discrepancy exists in Japan between written company law and its actual practice, foreign observers have difficulties in properly understanding the hierarchy and distribution of representative powers in Japanese boards. Neither English nor German concepts and legal terms are completely suitable for translating the Japanese titles and positions within the management. Current criticism not withstanding, the author regards the present system as being better than its reputation, and thus does not expect the recent reforms to lead to major changes. (The Editors)